Constructing qualitative energy concepts in a formal educational context with 6 - 7 year old students - DIMITRIS KOLIOPOULOS; MYRTO ARGYROPOULOU (Metaichmio Publications, 2011)
The research presented in this paper is a preliminary empirical study of primary school children's ability to construct a qualitative explanatory model for the 'energy' concept. The research results are particularly encouraging since it seems that 6-7 year old children are able, following a relevant teaching intervention, to utilize a linear causal reasoning and construct a preliminary energy model. Through the use of this model, the children are able to describe natural phenomena, such as the lighting of a lamp or the movement of a small motor using a battery or a photovoltaic cell.